1986
DOI: 10.1002/ajim.4700100314
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, lung function, and igg4 levels against pig antigens in a sample of dutch pig farmers

Abstract: In 1983 we distributed a postal questionnaire with 30 questions about the locomotor system, respiratory tract, the skin, and general health condition and about health hazards in the work environment to a sample of farmers. In addition, we asked the farmers to express their opinion about what they experienced as the main health hazards in their work environment.The questionnaire was sent to 1,895 randomly selected farmers. Main occupation is farming in one of the eight categories; the farmers were registered by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 0 publications
3
33
0
1
Order By: Relevance
“…There are large differences in the report ed incidence of respiratory ailments, such as chronic bronchitis, and in th e functional impairment observed. Som e studies ha ve reported a very high prevalence of cough and sputum production for these workers (2-4), while others found fewer symptomatic subjects (5,6). Similar differences can be found for the number o f subjects with abnormal pulmonary fun ctions (5,7).…”
supporting
confidence: 65%
See 3 more Smart Citations
“…There are large differences in the report ed incidence of respiratory ailments, such as chronic bronchitis, and in th e functional impairment observed. Som e studies ha ve reported a very high prevalence of cough and sputum production for these workers (2-4), while others found fewer symptomatic subjects (5,6). Similar differences can be found for the number o f subjects with abnormal pulmonary fun ctions (5,7).…”
supporting
confidence: 65%
“…Som e studies ha ve reported a very high prevalence of cough and sputum production for these workers (2-4), while others found fewer symptomatic subjects (5,6). Similar differences can be found for the number o f subjects with abnormal pulmonary fun ctions (5,7). Some of these differences can be explained by dif fer ences in study populations and differences in the swine building enviro nme nts.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Αυτή η κατάσταση θεωρείται διαφορετική από το άσθμα και ακούει στον όρο "ασθματοειδές σύν δρομο" (asthma-like syndrome). Ωστόσο, εργαζόμενοι με άσθμα αναφέρεται ότι μπορεί να παρουσιάσουν έντονα συμπτώματα λόγω του ερεθισμού από τη σκόνη και τα α έρια του συγκεκριμένου περιβάλλοντος, παρ' ότι κάτι τέ τοιο δεν έχει επαρκώς τεκμηριωθεί 29 . Συμφωνά με κάποι ους ερευνητές, η αυξημένη ανταπόκριση των εργαζομέ νων στη χορήγηση μεταχολίνης, μπορεί να αποτελεί και ένδειξη φλεγμονής των αεραγωγών 30 " 33 .…”
Section: αναπνευστικά προβλήματα των εργαζομένων σε βιομη χανικού τύπunclassified